Exploring Functional Differences between the Right and Left Ventricles to Better Understand Right Ventricular Dysfunction. (30th August 2021) - Bernal-Ramirez, Judith; Díaz-Vesga, Magda C.; Talamilla, Matias; Méndez, Andrea; Quiroga, Clara; Garza-Cervantes, Javier A.; Lázaro-Alfaro, Anay; Jerjes-Sanchez, Carlos; Henríquez, Mauricio; García-Rivas, Gerardo; Pedrozo, Zully
Abstract : The right and left ventricles have traditionally been studied as individual entities. Furthermore, modifications found in diseased left ventricles are assumed to influence on right ventricle alterations, but the connection is poorly understood. In this review, we describe the differences between ventricles under physiological and pathological conditions. Understanding the mechanisms that differentiate both ventricles would facilitate a more effective use of therapeutics and broaden our knowledge of right ventricle (RV) dysfunction. RV failure is the strongest predictor of mortality in pulmonary arterial hypertension, but at present, there are no definitive therapies directly targeting RV failure. We further explore the current state of drugs and molecules that improve RV failure in experimental therapeutics and clinical trials to treat pulmonary arterial hypertension and provide evidence of their potential benefits in heart failure.